KESALAHAN AFIKSASI DALAM KARANGAN NARASI MAHASISWA THAILAND (Affixation Error in Narrative Essays Written by Thai Students) - Syamsul Ghufron; Yasmee Sohkuning; Markub Markub (Balai Bahasa Sulawesi Selatan, 2021)
AbstractThis study aims to identify affixation errors in Thai students’ narrative essays. The study is a qualitative descriptive study, with the data source being narrative essays written by Thai students. The participants in this study were 22 Thai students from Unisda Lamongan. Data were collected and analyzed for four months, May to July of 2018. Data were collected using documentation, listening, and note-taking techniques with the data corpus sheet instrument. Data were analyzed using Ellis and Sridhar’s language error analysis steps, which included (1) collecting error samples, (2) identifying errors, (3) explaining errors, (4) classifying errors, (5) evaluating errors, and (6) concluding the error analysis results. The source triangulation technique had used to determine the data’s validity by comparing and re-examining the degree of confidence of the data. The results showed 109 affixation errors with 2% errors in determining the original form, 27% errors in assimilating and preserving phonemes, 68% errors in removing affixes, 3% errors in choosing morphs, and 1% errors in selecting affixes. According to the findings of this study, each language has unique characteristics that set it apart from others. These differences frequently result in language learning difficulties and language errors. AbstrakTujuan umum penelitian ini adalah mendeskripsikan kesalahan afiksasi dalam karangan narasi mahasiswa Thailand. Penelitian ini tergolong penelitian deskriptif kualitatif dengan sumber data berupa karangan narasi mahasiswa Thailand. Subjek penelitian ini adalah 22 mahasiswa Thailand di Unisda Lamongan. Data dikumpulkan dan dianalisis selama empat bulan: April—Juli 2018. Data dikumpulkan dengan teknik dokumentasi, teknik simak, dan teknik catat dengan instrumen lembar korpus data. Data dianalisis dengan langkah-langkah kerja analisis kesalahan berbahasa Ellis dan Sridhar yang meliputi (1) mengumpulkan sampel kesalahan, (2) mengidentifikasi kesalahan, (3) menjelaskan kesalahan, (4) mengklasifikasi kesalahan, (5) mengevaluasi kesalahan dan (6) menyimpulkan hasil analisis kesalahan. Dalam menentukan keabsahan data digunakan teknik triangulasi sumber dengan cara membanding-bandingkan dan memeriksa kembali derajat kepercayaan data. Hasil penelitian menunjukkan bahwa terdapat 109 kesalahan afiksasi dengan perincian sebagai berikut: 2% kesalahan penentuan bentuk asal, 27% kesalahan peluluhan dan pengekalan fonem, 68% kesalahan pelesapan afiks, 3% kesalahan pemilihan morf, dan 1% kesalahan pemilihan afiks. Implikasi penelitian ini adalah setiap bahasa memiliki karakteristik yang berbeda dengan bahasa lain.Perbedaan ini sering menimbulkan kesulitan belajar bahasa dan kesalahan bahasa.